Efeitos da fertirrigação com efluente de indústria de laticínios nos atributos do solo e na produção de mudas de eucalipto - Fachim, Adriana Zulian (2018)
Dairy products are characterized by being potentially polluting agroindustries because of the organic load of their liquid effluents. The high cost of water abstraction and treatment, as well as the imposition of environmental legislation,has been increasingly restrictive in the issue of effluent discharges, which has driven industries to implement effluent reuse systems. The application in the soilof treated effluent from the dairy industry (ETL), through the fertirrigation of eucalyptus seedlings, appears as an attractive option to supply nutrients and water to the plant, besides constituting a supplemental process of treatment or final disposal for this industrial wastewater. The objective of this study was to evaluate the effects of the disposal of treated effluent from a dairy industry on thesoil, that is, on the physical and chemical characteristics of the soil and on growth,morphological characteristics, nutritional status of seedlings of Eucalyptus urograndis. For this, the physical-chemical characterization of the effluent was carried out, and 30 experimental units were assembled in plastic buckets of 20 liters, divided in two plots, filled with the use of two separate sites, where 50% were filled using only soil already fertigated with the effluent in question and the remaining 50% filled only with soil removed from an area composed of remnants of native vegetation, where there was no contact with the wastewater. They werecultivated with the Eucalyptus urograndis species in the two plots that were submitted to 5 manually applied fertirrigation slides and defined as a function of the flow already applied by the company. After fertigation with the ETL for a periodof 180 days, there was a visible difference in growth and diameter between soil fertigation (SF) and non-fertigation (SFN), varying according to the ETL slides applied. The SNF presented a greater increase of the measurements compared to the SF, being the best response for the growth variable T3 with application rateof 200 ml ETL / day, and for the variable diameter the treatment that presented the best response was the T4 with application of 400 ml of ETL / day. In relation to the nutrients, it was also possible to verify the difference between SF and SNF,and showed a significant interaction for the variables N, P, K, Ca, Mg, S, , Ca, Mg, S, Fe, Zn, Mn and Bo for the nutrients in relation to the plot of soil in which the eucalyptus seedlings were grown. This difference between the two soil plots,the retention capacity and the assimilation of nutrients, shows that along with theeffluent application layer, the physical and chemical characteristics of the soil aredirectly related to the soil use factor before the experiment.